Soccer in the West: the World game in Australia's western periphery - Moore, Philip (Routledge - Taylor & Francis Group, 2009)
This study examines aspects of the history of soccer (Association Football) in Perth, Western Australia. The game was introduced in the late nineteenth century but it did not become central in the local sporting calendar. The game was reborn with the arrival of the ‘new Australians’ after the Second World War yet it remained marginal. Soccer’s place in Perth has often been represented as being due to the overwhelming ethnic involvement in the sport, as in other parts of Australia, but there is more to the story than such a reductionist explanation. Adopting a figurational approach this study examines established and outsider relations in the development of the game in Western Australian society. The account that emerges is of a complex organizational struggle over control of the sport. The focus on established and outsider relationships in a figurational context provides a useful way of accounting for this history.